MULTI-OBJECTIVE OPTIMIZATION DESIGN FOR CUTTING MECHANISM OF ROADHEADER BASED ON IMPROVED GENETIC ALGORITHM - MAO Jun; PAN DeWen; XIE Miao; ZHENG GuangHui (Jixie qiangdu)
The comprehensive performance of cutting mechanism of roadheader is decided by cutting dust,quantity of pick consumption,specific density consumption,load fluctuation and production efficiency. This paper takes motion parameters and structure parameters of cutting mechanism for design variables and optimizes multi-objective function of comprehensive performance of cutting mechanism based on the improved genetic algorithm. Optimization results show that cutting dust,quantity of pick consumption,specific density consumption and load fluctuation of roadheader are decreased accordingly and productivity is increased significantly,which effectively improve the whole performance of the machine and accord with development trend of the roadheader in line with the current and future.